1997
DOI: 10.1099/0022-1317-78-4-847
|View full text |Cite
|
Sign up to set email alerts
|

Infection with AIDS-related herpesviruses in human immunodeficiency virus-negative infants and endemic childhood Kaposi's sarcoma in Africa.

Abstract: Novel herpesviruses have been described recently. These include human herpesviruses 6, 7 and 8 (HHV-6, -7, -8). HHV-6 has at least two strain groups, variants A and B. The B strains are predominant in the West and can account for over 97 % of infections in infants. In contrast, the A strains are rare and the few well-characterized isolates have been from adult African AIDS patients. It is not clear whether the HHV-6 variant A strains are AIDSrelated and/or whether they can also be acquired as childhood infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 49 publications
(59 reference statements)
6
82
1
2
Order By: Relevance
“…Of these, three studies identified evidence of KSHV-DNA in peripheral blood cells (Chang et al, 1996;Kasolo et al, 1997;Belec et al, 1998), two used a lytic antibody assay alone (He et al, 1998;Lampinen et al, 2000), five used a latent antibody assay alone Ariyoshi et al, 1998;Bestetti et al, 1998;Bourboulia et al, 1998;Sitas et al, 1999) and 18 used both a lytic and a latent assay (Lennette et al, 1996;Simpson et al, 1996;Mayama et al, 1998;Olsen et al, 1988;Ablashi et al, 1999;Andreoni et al, 1999Andreoni et al, , 2002Enbom et al, 1999;Gessain et al, 1999;Wilkinson et al, 1999;Engels et al, 2000;Rezza et al, 2000;Gaye Serraino-Diallo et al, 2001;Kakoola et al, 2001;Nuvor et al, 2001;Serraino et al, 2001;Wawer et al, 2001). The results are presented in Table 1, together with the estimated cumulative incidence of Kaposi's sarcoma in men aged 0 -64 years in the period before HIV infection (Cook-Mozaffari et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, three studies identified evidence of KSHV-DNA in peripheral blood cells (Chang et al, 1996;Kasolo et al, 1997;Belec et al, 1998), two used a lytic antibody assay alone (He et al, 1998;Lampinen et al, 2000), five used a latent antibody assay alone Ariyoshi et al, 1998;Bestetti et al, 1998;Bourboulia et al, 1998;Sitas et al, 1999) and 18 used both a lytic and a latent assay (Lennette et al, 1996;Simpson et al, 1996;Mayama et al, 1998;Olsen et al, 1988;Ablashi et al, 1999;Andreoni et al, 1999Andreoni et al, , 2002Enbom et al, 1999;Gessain et al, 1999;Wilkinson et al, 1999;Engels et al, 2000;Rezza et al, 2000;Gaye Serraino-Diallo et al, 2001;Kakoola et al, 2001;Nuvor et al, 2001;Serraino et al, 2001;Wawer et al, 2001). The results are presented in Table 1, together with the estimated cumulative incidence of Kaposi's sarcoma in men aged 0 -64 years in the period before HIV infection (Cook-Mozaffari et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Four major clinical forms have since been described [Giraldo et al, 1989;Martin et al, 1993]: (1) epidemic or acquired immunodeficiency syndrome AIDS-associated; (2) classic; (3) African endemic; and (4) immunosuppressionassociated (iatrogenic) Kaposi's sarcoma [Giraldo et al, 1989;Beral et al, 1990;Martin et al, 1993]. African endemic Kaposi's sarcoma clusters among Africans from East and Central Africa and accounts for 3-18% of all malignancies in these regions [Martin et al, 1993;Gompels and Kasolo, 1996;Lennette et al, 1996;Kasolo et al, 1997]. Since the start of the AIDS epidemic and the rapid spread of human immunodeficiency virus type 1 (HIV-1) in subSaharan Africa, differentiation between African endemic and epidemic Kaposi's sarcoma has become more difficult; presently the epidemic form is diagnosed predominantly in African patients [Matondo, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…HHV-8 is present in all Kaposi's sarcoma lesions and is also associated with the rare AIDS-related body cavity-based B-cell lymphoma, non-AIDS-associated body cavity-based B-cell lymphomas, and multicentric Castleman's disease [Cesarman et al, 1995Boshoff et al, 1995;Huang et al, 1995;Soulier et al, 1995]. HHV-8 was detected in 8% of infants<15 months of age in Zambia, where a linear increase in seroprevalence with age was noticed that reflects the endemic nature of HHV-8 infection (47% in 14-19-year-olds to 71% in persons aged≥50 years) [Kasolo et al, 1997;Olsen et al, 1998]. A high seroprevalence rate of 84-100% was also found in the non-Kaposi sarcoma endemic regions of West Africa (The Gambia and the Ivory Coast) [Lennette et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…HHV-6 is the causative agent of the sixth childhood disease exanthem subitum (6). In industrialized countries, primary HHV-6 infections are almost always caused by the B variant (7) although primary infections with variant A have been reported in Africa (8). Other complications of primary HHV-6 infection include hepatitis (9), meningitis (10), fatal hemophagocytic syndrome (11), and fatal disseminated infection (12).…”
mentioning
confidence: 99%